Pengaruh Tayangan Konten Review Film pada Channel Youtube Cine Crib Terhadap Keputusan Menonton Subscribers - Akbar, Ilham; Suyanto, Suyanto; Ismandianto, Ismandianto; Awza, Rusmadi (Fakultas Ekonomi dan Ilmu Sosial Program Studi Ilmu Komunikasi Universitas AMIKOM Yogyakarta, 2022)
Cine Crib is a youtube channels that focuses on the most popular movie review content in Indonesia. Through his Youtube channel, Cine Crib consistently uploads film review videos and has gained 239,000 subscribers. The Cine Crib film review videos has the potential to influence the decision of Cine Crib subscribers to watch the reviewed film. Therefore, this study aims to see the influence of film review content on the Cine Crib youtube channel for the subscriber's watching decision with quantitative research method in an explanation format. Through the slovin formula, 400 respondents were obtained who are subscribers of Cine Crib using simple random sampling as sampling technique. After the questionnaire was gathered via google form, thedata found were then processed using SPSS for windows version 25 with simple linear regression analysis as a data analysis technique. The results of this study indicate that there was an influence of film review content on the Cine Crib youtube channel on the subscriber's watching decision by 34% who fell into the weak category, and the rest were influenced by other variables that were not included in this study by 66%. With these results, it can be concluded that the impression of Cine Crib's film review content does have an influence on her subscribers, but the influence exerted tends to be weak and the impression of review content on Cine Crib's Youtube channel is not the only variable that affects her subscribers' viewing decisions.